Identity theory - Burke, Peter J. (Peter James), 1939-; Stets, Jan E. (New York ; Oxford : Oxford University Press, 2009)
The authors describe and illustrate identity theory, a social psychological theory that attempts to understand identities their sources in interaction and society, their processes of operation, and their consequences for interaction and society from a sociological perspective.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Identity (Psychology)